Study protocol of a parent-focused child feeding and dietary intake intervention: the feeding healthy food to kids randomised controlled trial - Duncanson Kerith; Burrows Tracy; Collins Clare (BMC, 2012)
Abstract Background Poor childhood nutrition is a more pervasive and insidious risk factor for lifestyle-related chronic disease than childhood obesity. Parents find it difficult to address the reported barriers to optimal child feeding, and to improve child dietary patterns. To impact at the population level, nutrition interventions need to be easy to disseminate, have a broad reach and appeal to parents while overcoming the barriers parents face when trying to improve child feeding behaviours. The Feeding Healthy Food to Kids (FHFK) Randomised Control Trial (RCT) examines the impact of providing low cost, self-directed nutrition and parenting resources to rural parents, on child dietary intake and parent-child feeding practices. Methods/Design Up to 150 parents of two-to-five year old children will be recruited in five rural Australian towns. Eligible, consenting parents will be randomly allocated to intervention or 12-month wait-list control groups. Intervention group parents will receive an interactive nutrition CD and parenting DVD, and be provided with instructions for optimal resource utilisation. Intervention and control group participants will also receive a generic nutrition and physical activity brochure and a physical activity resource to blind participants to group allocation. Primary outcome measures are dietary intake of vegetables (serves/day), fruit and energy dense nutrient poor foods (serves/day and %Energy). Secondary outcome measures are total energy (kCal), other food groups (serves/day and %Energy), key nutrients (mg/day), child feeding domains and parenting style domains. Analysis of dietary outcome measures, child feeding and parenting domains will be conducted on an intention-to-treat basis and compared at baseline, three and 12 months using the random effects model, using STATA software. Details of the methodological aspects of recruitment, inclusion criteria, randomisation and statistical analysis are described. Discussion This paper will add to existing research examining child feeding practices and dietary intake of young children, by specifically focusing on the efficacy of an RCT that has the potential to be implemented at a population level. The correlation of the RCT outcomes with parents' perceptions about child feeding practices and children's dietary intake of their children in a subsequent qualitative study will further contribute to this emerging area of research. Trial registration Australian Clinical Trials Registration Number: ACTRN12609000356268